2013
DOI: 10.1890/es13-00125.1
|View full text |Cite
|
Sign up to set email alerts
|

Using tree functional diversity to evaluate management impacts in a subtropical forest

Abstract: Abstract. The trait-based approach has received much research attention as it provides a heuristic framework for evaluating the ecological impacts of anthropogenic activities on communities and ecosystems. In this study, functional diversity (or structure) measures, such as functional richness, functional evenness, functional divergence, and functional composition, were used to examine management impacts on subtropical forests on the Ryukyu Islands of Japan. Functional indices were compared in tandem with taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 62 publications
2
29
0
Order By: Relevance
“…Indices based on both species traits and abundances (e.g., functional divergence or specialization) cannot provide evidence of species extirpations or local extinctions along disturbance gradients (Mouillot et al 2012). However, our results showed that secondary succession affects the patterns of niche differentiation of the species forming the functional space of secondary forests (see Maeshiro et al 2013). In addition, in secondary forests with intermediate levels of disturbance, species with combinations of traits that are vulnerable to disturbance could coexist with disturbance-tolerant species.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Indices based on both species traits and abundances (e.g., functional divergence or specialization) cannot provide evidence of species extirpations or local extinctions along disturbance gradients (Mouillot et al 2012). However, our results showed that secondary succession affects the patterns of niche differentiation of the species forming the functional space of secondary forests (see Maeshiro et al 2013). In addition, in secondary forests with intermediate levels of disturbance, species with combinations of traits that are vulnerable to disturbance could coexist with disturbance-tolerant species.…”
Section: Discussionmentioning
confidence: 70%
“…However, our results showed that secondary succession affects the patterns of niche differentiation of the species forming the functional space of secondary forests (see Maeshiro et al . ). In addition, in secondary forests with intermediate levels of disturbance, species with combinations of traits that are vulnerable to disturbance could coexist with disturbance‐tolerant species.…”
Section: Discussionmentioning
confidence: 97%
“…their functional traits) drives multiple ecosystem functions (e.g. productivity and biogeochemical cycling) and their functional diversity is a proxy for ecological redundancy within forest ecosystems (Maeshiro et al ., ). Therefore our results indicate that the redundancy of ecosystem functions should depend critically on geographical patterns of climatic factors.…”
Section: Discussionmentioning
confidence: 97%
“…Information on the potential maximum stem height (m) of each species was assembled from literature sources (Satake et al, 1989). Maeshiro et al (2013) provide a more detailed description of the trait measurements.…”
Section: Trait Datamentioning
confidence: 99%
“…Clearcut-logging (or clearcutting) provides an experimental setting in which researchers can analyze reassembly patterns of functional and phylogenetic structure through species sorting related to anthropogenic disturbance (Maeshiro et al 2013;Kusumoto et al 2015;Toyamaetal. 2015).…”
Section: Introductionmentioning
confidence: 99%